Time-dependent deformation analysis of the surrounding rock mass around a tunnel. Issue 2 (October 2020) - Fu, Teng-Fei; Xu, Tao; Nara, Yoshitaka; Xue, Yan-Chao; Heng, Zhen; Yuan, Yang
Abstract: A numerical time-dependent model is established by incorporating the stress corrosion model into the three-dimensional discrete element grain-based model (3DEC-GBM) to analyze the fracture evolution and instability mechanism of the surrounding rock mass around a circular tunnel. The surrounding rock of the tunnel is assumed to be made from intact Yunnan sandstone formation, whose material properties were found using laboratory experiments (ignoring scale effects). The mesoscale mechanical stress corrosion parameters in the model are calibrated to reproduce the time-independent and -dependent deformation and failure of Yunnan sandstone observed in a laboratory. The model is validated against laboratory data and then further applied to analyze the time-independent and -dependent deformation of the surrounding rock of the tunnel. The fracture evolution around the tunnel instability is numerically visualized. The failure zone around the tunnel gradually extends deeper into the surrounding rock with time, and the location of failure at the roof and floor of the circular tunnel becomes more evident as the lateral pressure coefficient increases. We conclude that the model is not only able to simulate the location of the concentrated tensile and shear stress around the tunnel but also has important theoretical guidance and practical significance for the long-term stability study of tunnels.